FROM THE HISTORY OF MIXED MARRIAGES. MARRIAGES WITH GYPSIES IN THE ROMANIAN SPACE IN THE 18TH AND FIRST HALF OF THE 19TH CENTURY. - Felea, Alina (Culture Management / Zarządzanie w Kulturze, 2013)
In the given article we will analyze marriages between Romanians (Moldovans) and Gypsies, and present the legal juridical framework regulating the issue of such marriages as well as the actual situation recorded in Ţara Moldova in the eighteenth century, and in the territory between the Prut and Dniester rivers in the fi rst half of the nineteenth century. The documents presented will include the descriptions of research sources including the code of laws issued in Ţara Moldova, charters issued by the Prince of Ţara Moldova, Ukases (decrees) issued in the Russian Empire, permission requests for marriages, consult requests of the priests offi ciating mixed marriages, as well as documents of the National Archive of Moldova. The marriages of Gypsies with Romanians can be examined simultaneously from two points of view: as mixed marriages from the ethnic point of view and mixed marriages from the social point of view. According to religious criteria, which were the basis for the legitimate family formation, the representatives of both ethnicities were to be Orthodox, so that there were no impediments to the marriage from the canonical point of view. Problems arised in connection with the social status of the Gypsies, who were considered to be subservient people.